The Influence of Parangtritis Coastal Geology Phenomena on Marine Tourism Activities in Yogyakarta - Muhtadi, Muhammad Ammar (Jurnal Geosains West Science, 2025)
This study examines the influence of Parangtritis’s coastal geological phenomena on marine tourism activities and their socio-economic impacts on local communities. Using a qualitative approach, data were collected through interviews with five local stakeholders, direct observations, and document analysis. Findings reveal that unique features such as sand dunes, cliffs, and tidal zones are central to the area's tourism appeal, attracting visitors for recreational and cultural experiences. However, environmental degradation, including dune erosion and waste management issues, poses significant challenges. The study emphasizes the need for sustainable tourism practices, community engagement, and collaborative management to preserve Parangtritis’s natural and cultural assets while supporting local livelihoods. Recommendations include eco-tourism initiatives, stricter regulations, and participatory management frameworks to ensure long-term sustainability.